The role of cultural schemata in inferential reading comprehension: an investigation in the Iranian EFL context - Khataee, Elnaz; Davoudi, Mohammad (Penerbit Universiti Kebangsaan Malaysia, 2018)
Reading is an important skill in many foreign language teaching situations and is valuable for both teachers and EFL students because it provides great opportunity for EFL learners to be exposed to the target language and improve their language proficiency by receiving appropriate input. For this purpose, 67 BA students, majoring in English language and literature at Hakim Sabzevari University were the participants. There were two groups of participants, one group served as the experimental group and the other as the control group. The students’ schema in experimental group was activated by giving them prior knowledge (background knowledge) while the participants in control group received no treatment. The results of the t-test showed that the means of experimental and control group on the three tests were significantly different. Thus, it can be concluded that, providing related cultural background about the text has a significant effect on inferential reading comprehension of Iranian EFL learners since readers are expected to attain the writers intended meaning by linking their existing information with what they read. Therefore, according to study’s reports it can be stated that conducting readers’ cross-cultural background knowledge is in fact a powerful instructional strategy to EFL reading comprehension. As an implication of the study, administrators can use certain programs to train language teachers on the appropriate methods of activating students’ schema before reading cultural texts.